Desenvolvimento de métodos eletroanalíticos para avaliação da capacidade antioxidante - Benjamin, Stephen Rathinaraj (2016)
This study investigated the antioxidant activity using biosensors based on carbon paste electrode (CPE) modified with crude extract of laccase (Pycnoporus sanguineus, activity 2019 U L-1) in different compositions. The biosensor consists of carbon nanotubes activated with DNA (CPEL-DNA: CN) showed the best sensitivity level, 0.0549 μA / μM and 1.2 uM detection limit (LOD) in the concentration range of 20-140 μM of rutin. This biosensor showed excellent stability over 10 days and reproducibility (RSD <5%). This biosensor was used to determine the total amount of phenol in coffee samples (expressed by the equivalent rutin) using electroanalytical technique. For the evaluation of its detection capability, the results were compared with other electroanalytical techniques using analytical basis as samples of commercial coffee from different countries. The CPL-DNA: CN was used to determine the total amount of phenol in coffee samples (expressed by the equivalent rutin). Thus, it was possible to propose the CPL as an analytical tool for the detection of phenols. In this research, we developed several studies using different CPE to investigate the antioxidant natural product profile such as coffee samples, dry extracts of acerola, obtained by cyclic voltammetry (CV),) differential pulse voltammetry (DPV) and square wave voltammetry (SWV), which allowed to conclude classes of antioxidants present in the samples. The quantitative determination of these compounds was performed using the standard addition method by differential pulse voltammetry and electrochemical index (EI) has been proposed for estimating the oxidizing potential between different samples. Carbon paste electrode was also investigated using the different quality control samples commercialized produced from acerola employing DPV for the quantification of ascorbic acid (AA) in all samples, where the limit of detection (LOD) and limit of quantification (LOQ) was 0.31 and 0.96 μM and with excellent recovery between 97.4 to 102.2% The DPPH tests were used to compare the antioxidant activity in coffee and acerola samples. The Folin-Ciocalteu method was used to estimate the antioxidant activity of rutin from coffee samples. These methods proposed had advantages such as simplicity of sample preparation and the speed of the analysis of antioxidant capacity.